Spinal manipulative therapy versus Graston Technique in the treatment of non-specific thoracic spine pain: design of a randomised controlled trial. - Crothers A; Walker B; French SD (Chiropractic & Osteopathy)
Background: The one year prevalence of thoracic back pain has been estimated as 17% compared to 64% for neck pain and 67% for low back pain. At present only one randomised controlled trial has been performed assessing the efficacy of spinal manipulative therapy (SMT) for thoracic spine pain. In addition no high quality trials have been performed to test the efficacy and effectiveness of Graston Technique® (GT), a soft tissue massage therapy using hand-held stainless steel instruments. The objective of this trial is to determine the efficacy of SMT and GT compared to a placebo for the treatment of non specific thoracic spine pain. Methods: Eighty four eligible people with non specific thoracic pain mid back pain of six weeks or more will be randomised to one of three groups, either SMT, GT, or a placebo (de-tuned ultrasound). Each group will receive up to 10 supervised treatment sessions at the Murdoch University Chiropractic student clinic over a 4-week period. Treatment outcomes will be measured at baseline, one week after their first treatment, upon completion of the 4-week intervention period and at three, six and twelve months post randomisation. Outcome measures will include the Oswestry Back Pain Disability Index and the Visual Analogue Scale (VAS). Intention to treat analysis will be utilised in the statistical analysis of any group treatment effects. Trial Registration: This trial was registered with the Australia and New Zealand Clinical Trials Registry on the 7th February 2008. Trial number: ACTRN12608000070336.